Rhodium‐Catalyzed Diastereoselective Cyclization of Allenyl‐Sulfonylcarbamates: A Stereodivergent Approach to 1, 3‐Aminoalcohol Derivatives. Issue 50 (15th November 2016) - Spreider, Pierre A.; Haydl, Alexander M.; Heinrich, Marc; Breit, Bernhard
Abstract: A diastereoselective and stereodivergent rhodium‐catalyzed intramolecular coupling of sulfonylcarbamates with terminal allenes is described and it provides selective access to 1, 3‐aminoalcohol derivatives, scaffolds found in bioactive compounds. The reaction is compatible with a large range of different functional groups, thus furnishing products with high diastereoselectivities and yields. Moreover, multigram scale reactions, as well as the application of suitable product transformations were demonstrated. Abstract : Either way : The diastereoselective and stereodivergent rhodium‐catalyzed intramolecular coupling of sulfonylcarbamates with terminal allenes permits the selective synthesis of N‐allylic 1, 3‐aminoalcohol derivatives. The reaction is compatible with a large range of functional groups and furnishes products with high diastereoselectivities and yields.